Assessment of a Situation Awareness Quality Improvement Intervention to Reduce Cardiac Arrests in the PICU. Issue 1 (January 2022) - Dewan, Maya; Soberano, Blaise; Sosa, Tina; Zackoff, Matthew; Hagedorn, Philip; Brady, Patrick W.; Chima, Ranjit S.; Stalets, Erika L.; Moore, Lindsey; Britto, Maria; Sutton, Robert M.; Nadkarni, Vinay; et al.
Abstract : OBJECTIVES: To use improved situation awareness to decrease cardiopulmonary resuscitation events by 25% over 18 months and demonstrate process and outcome sustainability. DESIGN: Structured quality improvement initiative. SETTING: Single-center, 35-bed quaternary-care PICU. PATIENTS: All patients admitted to the PICU from February 1, 2017, to December 31, 2020. INTERVENTIONS: Interventions targeted situation awareness and included bid safety huddles, bedside mitigation signs and huddles, smaller pod-based huddles, and an automated clinical decision support tool to identify high-risk patients. MEASUREMENTS AND MAIN RESULTS: The primary outcome metric, cardiopulmonary resuscitation event rate per 1, 000 patient-days, decreased from a baseline of 3.1–1.5 cardiopulmonary resuscitation events per 1, 000 patient-days or by 52%. The secondary outcome metric, mortality rate, decreased from a baseline of 6.6 deaths per 1, 000 patient-days to 3.6 deaths per 1, 000 patient-days. Process metrics included percent of clinical deterioration events predicted, which increased from 40% to 67%, and percent of high-risk patients with shared situation awareness, which increased from 43% to 71%. Balancing metrics included time spent in daily safety huddle, median 0.4 minutes per patient (interquartile range, 0.3–0.5), and a number needed to alert of 16 (95% CI, 14–25). Neither unit acuity as measured by Pediatric Risk of Mortality III scores nor the percent of deaths in patients with do-not-attempt resuscitation orders or electing withdrawal of life-sustaining technologies changed over time. CONCLUSIONS: Interprofessional teams using shared situation awareness may reduce cardiopulmonary resuscitation events and, thereby, improve outcomes. Abstract : Supplemental Digital Content is available in the text.